Practical epidemiology : using epidemiology to support primary health care - Vaughan, J Patrick; Victora, Cesar; Chowdhury, A. M. Raza (Oxford : Oxford University press, 2021)
"The 2030 Agenda for Sustainable Development was adopted by all United Nations Member States in 2015. There are 17 Sustainable Development Goals (SDGs) that were agreed by all high, middle and low-income countries (previously referred to as developed and developing countries) that aim to end poverty by adopting strategies to improve health and education, reduce inequality, and spur on economic growth while at the same time also tackling climate and environmental changes. The SDGs build on the earlier eight global Millennium Development Goals (MDGs) that aimed to reduce extreme poverty by 2015"--
Includes index.
AAL
Keywords: Epidemiology -- Developing countries; Primary health care -- Developing countries